Simenon, un auteur et ses lecteurs : une économie de la grandeur - Véronique Rohrbach (Contextes)
In order to grasp the concrete reception of a writer, this study focuses on readers’ letters addressed to Simenon. It shows what the author – a figure at the crossroads of the person, the character of fiction (Maigret) and the celebrity – does to and for its readers. In seeking to outline principal features of the writer/readers relationship, this article also pays attention to the tensions between symbolic and economic values borne together by an author present at the same time on the commercial, media and literary scenes. In the end, the letters written by “ordinary” people to Simenon allow to understand forms of “an attachment to the great individuals” (Heinich).